Predictors of camptocormia in patients with Parkinson's disease: A prospective study from southwest China. (July 2018) - Ou, Ruwei; Liu, Hui; Hou, Yanbing; Song, Wei; Cao, Bei; Wei, Qianqian; Yuan, Xiaoqin; Chen, Yongping; Zhao, Bi; Shang, Huifang
Abstract: Background: Camptocormia is becoming increasingly recognized as a prominent phenomenon in Parkinson's disease (PD). Objective: This study aims to investigate the clinical predictors of future camptocormia in a cohort of PD patients. Methods: A total of 263 PD patients without camptocormia were prospectively monitored for approximately 3 years. The end-point was the occurrence of camptocormia. Results: Overall, camptocormia was observed in 23 patients (8.7%) during the study period. The following variables including the proportion of males; age; disease duration; total levodopa equivalent daily dosage; Unified PD Rating Scale (UPDRS) III score; Hoehn and Yahr stage; the percentages of festination, freezing of gait and falls; and the subscores (e.g., "problems having sex") and frequencies (e.g., "forget to do things") of the Non-Motor Symptoms Scale were significantly higher in patients with camptocormia compared to those variables in patients without camptocormia ( P  < 0.05). Patients with camptocormia showed lower "orientation" subscore of the Montreal Cognitive Assessment scale than patients without camptocormia ( P  < 0.05). The binary logistic regression model indicated that the presence of camptocormia was associated with male sex (OR = 6.758, P  = 0.001), a higher UPDRS III score (OR = 1.099, P  = 0.001), a higher sexual dysfunction score (OR = 1.033, P  = 0.038) and a lower orientation score (OR = 0.392, P  = 0.018). Conclusions: Camptocormia may emerge as PD progresses. Male patients and those with sexual dysfunction or disorientation are likely to present with camptocormia in the future. Highlights: Camptocormia emerges as PD progresses. Male patients are likely to develop future camptocormia. Patients with sexual dysfunction are likely to develop future camptocormia. Disorientation may be a predictor for camptocormia.